Construction of an Integrated Social Vulnerability Index to Identify Spatial Variability of Exposure to Seismic Hazard in Pahang, Malaysia - Sauti, Noor Suhaiza; Daud, Mohd Effendi; Kaamin, Masiri (International Information and Engineering Technology Association (iieta), 2020)
Devastating effects of natural disasters dynamically depends on the vulnerability components of a specific area. Therefore, assessing vulnerability is necessary to estimate the earthquake risk. This paper argues for a multidisciplinary method that integrates social vulnerability into the seismic risk analysis in Pahang. The methodology specifically relies on; (1) the development on a set of social indicators using multivariate data analysis to identify and evaluate the local characteristics that contribute to the vulnerability and risk of inhabitants of district space; and (2) the application of Geographical Information System (GIS) technology for generating and mapping the spatial pattern of social vulnerability index for seismic hazard in Pahang, Malaysia that was based on the classification of its exposure level. The classes of a social vulnerability index map were overlaid with a seismic hazard map that was proposed by JMG (Mineral and Geoscience Department Malaysia) through the use of map algebra functions in GIS tools. Results for social vulnerability map showed that, majority of the study area are in relatively low to moderate level except for Kuantan district, which is highly vulnerable. Meanwhile, the combination of the social vulnerability map and seismic hazard map reveals that, districts in the central parts of the region are the most highly exposed to earthquake threats, whereas in the eastern part it demonstrates the low level of exposure to seismic hazard (with the exception for the Kuantan district, where it is highly vulnerable). The proposed method provides useful information on the spatial variability of exposure vulnerability to seismic hazard that could enhance the earthquake preparedness and mitigation.